Dementia Subtypes: A Study From Dementia Clinic In A Referral Neuroscience Hospital, Bangladesh - Hassan, Mohammad Sayeed; Uddin, Mohammad Nur; Shams, Samina; Hossain, Shadad; Sarker, Mouri; Sonia, Sheikh Farjana; Mehrab, Rafi; Yusuf, Abdullah; Rahman, Aminur; Hakim, Maliha (Bangladesh Journal of Medicine, 2025)
Background: Dementia is one of the major causes of disability and dependency among older people globally but still it is not explored very well in most parts of the world particularly for low-income and middle-income countries. The aim of study was to explore the subtypes of dementia among patients attending the outdoor dementia clinic at a referral tertiary care hospital in Bangladesh. Methods: This cross-sectional study was carried out in weekly dementia clinic of Department of Neurology at National Institute of Neurosciences and Hospital (NINS&H), Dhaka, Bangladesh from January 2020 to December 2023 for a period of 4 years. Consecutive patients attending this clinic with history suggestive of dementia were enrolled in this study. Data were collected through a predesigned questionnaire containing information about demography, clinical features, brain imaging and laboratory findings of patients. This study included all patients aged ³18 years, both male and female, who attended with subjective memory and other cognitive impairment complaints. Results: The age range was from 25 to 100 years with mean age of 66.04 (±SD 10.61) years with a male-to female ratio of 1.54: 1. There was urban (67.4%) predominance. In 435 patients, the commonest subtype of dementia was Alzheimer’s disease (n= 219, 50.3%). The second most common subtype was vascular dementia (n= 75, 17.2%) followed by mixed dementia (n= 60, 13.8%). Frontotemporal dementia, Parkinson’s disease dementia, and dementia with Lewy bodies were diagnosed in 22 (5.1%), 13 (3 %) and 6 (1.4%) cases respectively. Most of the patients (n= 141, 32.9%) had mild dementia whereas 121 (27.8%) patients had moderate dementia. Only 35 (8%) patients had severe dementia, 72 (16.6%) patients had mild cognitive impairment (MCI). Conclusion: Dementia is a major morbidity with a higher prevalence among elderly males. Alzheimer’s disease is the most common subtype of dementia in Bangladesh. Bangladesh J Medicine 2025; 36(3): 123-128